The Effect of L-tyrosine on Thebaine Production in Cell Suspension Culture of Iranian Poppy (Papaver bracteatum) - R Farjaminezhad; N Zare; R Asghari-Zakaria; M Farjaminezhad (Institue of Medicinal Plants, ACECR, 2016)
Background: Using of elicitors and different compounds in cell suspension culture is an effective strategy for enhancement and improvement of important secondary metabolites production in in vitro conditions. Objective: Evaluation of the effects of L-tyrosine and its combination with biological elicitors such as chitosan and salicylic acid on thebaine production in Iranian poppy cell suspension cultures at different days after elicitation. Methods: Different concentrations of L-tyrosine (1 and 2 mM) individually and in combination with chitosan (100 mg/L) and salicylic acid (50 mg/L) was applied on cell cultures, and then, pH and EC of medium, and also thebaine content of cells were measured on 2, 4 and 6 days after treatment. Results: The highest thebaine content of cells (42.30 mg/L) was obtained in 1 mM L-tyrosine on six days after treatment, which was significantly higher than the control. In addition, there was a relation between thebaine content of cells and pH and ECof culture medium. With increasing the thebaine content of cells, pH of medium was increased and EC of medium was decreased. Conclusion: Feeding of Iranian poppy cell suspension cultures with L-tyrosine (precursor of alkaloids biosynthesis) was improved thebaine production. So that, 1 mM L-tyrosine increased the thebaine content of cells up to 22.26-fold compared with control.